Book Review of "Breaking Out II: The Complete Guide to Building a Positive LGBTI Identity" - Hancock, Ryan (Canadian Journal of Counselling and Psychotherapy, 2012)
This book is an excellent hands-on manual for helping LGBTI individuals develop a positive self-image and acceptance of who they are within society. The author provides recommendations for better understanding one’s self and connecting to LGBTI culture and the dominant culture, while also addressing the unique concerns of LGBTI adolescents. The author offers a step-by-step guide for improving one’s self-esteem and self-acceptance through the use of worksheets, charting, visualization, goal-setting, and other experiential exercises. Also included are self-evaluations that assist readers in gauging their own improvement in the skill areas discussed.